Decreased serum level of sphingosine‐1‐phosphate: a novel predictor of clinical severity in COVID‐19. Issue 1 (9th December 2020) - Marfia, Giovanni; Navone, Stefania; Guarnaccia, Laura; Campanella, Rolando; Mondoni, Michele; Locatelli, Marco; Barassi, Alessandra; Fontana, Laura; Palumbo, Fabrizio; Garzia, Emanuele; Ciniglio Appiani, Giuseppe; Chiumello, Davide; et al.
Abstract: The severity of coronavirus disease 2019 (COVID‐19) is a crucial problem in patient treatment and outcome. The aim of this study is to evaluate circulating level of sphingosine‐1‐phosphate (S1P) along with severity markers, in COVID‐19 patients. One hundred eleven COVID‐19 patients and forty‐seven healthy subjects were included. The severity of COVID‐19 was found significantly associated with anemia, lymphocytopenia, and significant increase of neutrophil‐to‐lymphocyte ratio, ferritin, fibrinogen, aminotransferases, lactate dehydrogenase (LDH), C‐reactive protein (CRP), and D‐dimer. Serum S1P level was inversely associated with COVID‐19 severity, being significantly correlated with CRP, LDH, ferritin, and D‐dimer. The decrease in S1P was strongly associated with the number of erythrocytes, the major source of plasma S1P, and both apolipoprotein M and albumin, the major transporters of blood S1P. Not last, S1P was found to be a relevant predictor of admission to an intensive care unit, and patient's outcome. Circulating S1P emerged as negative biomarker of severity/mortality of COVID‐19 patients. Restoring abnormal S1P levels to a normal range may have the potential to be a therapeutic target in patients with COVID‐19. Synopsis: The study demonstrates that patients with COVID‐19 experience a significant reduction of serum sphingosine‐1‐phosphate (S1P). The decrease of S1P associates with the number of erythrocytes, a major source of circulating S1P, as well as with the levels of high‐density lipoprotein (HDL)/apolipoprotein M (apoM) and albumin, the most important transporters of circulating S1P. The serum levels of S1P, erythrocytes, apoM and albumin are lower in COVID‐19 patients admitted to intensive care unit (ICU) than in no‐ICU patients. Serum S1P negatively correlates with clinical parameters including Pneumonia Severity Index and days of hospitalization. S1P levels exhibit a strong power in predicting both ICU admission and mortality. Abstract : The study demonstrates that patients with COVID‐19 experience a significant reduction of serum sphingosine‐1‐phosphate (S1P). The decrease of S1P associates with the number of erythrocytes, a major source of circulating S1P, as well as with the levels of high‐density lipoprotein (HDL)/apolipoprotein M (apoM) and albumin, the most important transporters of circulating S1P.